(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Macular edema (ME) develops in 60-100% of patients with retinal vein occlusion (RVO). ME becomes chronic with a decrease in visual acuity in 1/3-2/3 of patients with RVO-associated ME. The gold standard of care to treat patients with macular edema associated with RVO is retinal laser photocoagula-tion. Purpose. To develop an evaluation system for severity of macular edema asso-ciated with retinal vein occlusion on a ground of morphometrical and clinical characteristics and to compare the efficacy of threshold and subthreshold retinal laser photocoagulation depending on this evaluation. Material and Methods. A total of 160 patients (160 eyes) with RVO-associated macular edema were included in the study. Laser photocoagulation was performed not before than three months of disease onset. Subthreshold and threshold laser photocoagulation of the macula was performed in 38 and 110 patients, respectively. 12 patients had resorption of edema so they required no laser treatment. The follow-up period was twelve months. The examination methods used have been described in our previous paper. Results. The heterogeneity analysis of the cohort of patients with RVO-associated ME was proposed. The clinical burden assessment was developed and criteria of macular edema severity were defined. There were four clusters that clearly differed in their clinical and morphometric characteristics. Subthreshold laser photocoagulation was shown to be more successful for patients with significant retinal ischemia and threshold laser photocoagulation was more successful for patients with the increased foveal thickness. Conclusions. Four cluster distribution of the RVO-associated ME patients made it possible to reduce the heterogeneity of the studied cohort since the defined clusters were homogenous in severity criteria; the patients had similar values within each cluster. Subthreshold photocoagulation was best for the significant ischemic area (>5 DD). For the foveal thickness >547 µm, most successful was threshold laser photocoagulation.